PERBANDINGAN KEUNTUNGAN USAHATANI PADI SAWAH DENGAN TEKNIK TANAM PINDAH DAN TEKNIK TANAM BENIH LANGSUNG DI DUMOGA UTARA KABUPATEN BOLAANG MONGONDOW - Leydia E. Rauw; Charles R. Ngangi; Eyverson Ruauw; Ribka M. Kumaat (COCOS, 2014)
ABSTRACTLeydia Esther Rauw. Comparative Advantage of Rice Farming with Moved Planting Techniques And Direct Seed Planting Techniques in North Dumoga Bolaang Mongondow Regency (under guidance of Charles R. Ngangi, as Chairman, Eyverson Ruauw and Ribka M. Kumaat as Members).The objective of this research is to determine the difference advantage with moved planting technique and direct seed planting technique in North Dumoga Bolaang Mongondow Regency.Methods of data collection was the survey method. The data collected consisted of primary data and secondary data. Primary data is data obtained from direct observation and interviews with the respondents based on a list of questions (koesioner), while the secondary data obtained from the relevant agencies and district offices in North Dumoga Farmer Water User Association. The population is all rice farmers consisting of 40 percent of the farmers who use the moved planting system and 60 percent of farmers using direct seed planting then randomly drawn sample (simple random sampling). For farmers with moved planting system was 15 responden and farmers with direct seed plants system was 15 responden.The results showed that there is a difference between the profit of moved planting technique and direct seed planting technique. Advantages of direct seed planting technique is greater than moved planting techniques although the cost of productivity and input factor of both planting techniques were not significantly different. Furthermore the largest cost used on rice paddy farming was labor costs.